A gestão de recursos humanos no setor calçadista: o caso de Franca- SP - Pitangui, Catarine Palmieri (2008)
The present work approaches the Human Resource organizational practices that characterize the industrial footwear sector. And, specifically, looks a relation betwen the modernization of the management of the human resources and the size of the searched companies. For such, a explanatory research between companies of small, average and great sizes in the Franca-SP footwear industry, a region with great representation in the national industrial sector. This sector is little tied with the ample transformations of the capital. The low barriers to the entrance that this sector presents, allow that people with a cultural source decrease changed themselves into entrepreneurs. The perception of these actors is come back toward the production, for the world of the work in itself, and not for an administrative perception. And this reflects in all the industrial sizes of this industry. Through structuralized interviews applied to the entrepreneurs and/or to the RH management of the considered sample, it was possible to evidence a picture of practical enterprises that characterize the Franca-SP industry of footwear in this direction. The results disclose that the practical ones related to the management of the employees in the searched companies, in its majority, approach to the practical ones of Personal Department. In this sample, only in two of great size searched companies exists a RH functional area with practices more evolved for the people administration.